Tax Evasion in a Unionised Economy - Laszlo Goerke (Institute for the Study of Labor (IZA), 2001)
In a unionised labour market, a substitution of a payroll for an income tax will not alter employment if tax obligations are fulfilled. However, if workers or firms can evade taxes this irrelevance result might no longer apply. This will especially be the case if the fine for tax evasion depends on undeclared income or on wage payments or if withholding regulations prevent optimal evasion choices. In such instances, tax evasion opportunities make the legal incidence of taxes an important determinant of their economic incidence and employment can rise with a substitution of an income for a payroll tax.
Keywords: H26; J64; H22; J51; 330; Economic incidence; legal incidence; penalty; tax evasion; trade union; Steuerkriminalität; Lohnsteuer; Einkommensteuer; Steuerwirkung; Lohnverhandlungstheorie; Gewerkschaft; Theorie